Stainless steel sheet with grain size and martensite phase in double-gradient distribution and preparation method of stainless steel sheet
Through axial cold rolling and heat treatment methods, the grain size and martensite phase content of stainless steel sheets were prepared, which solved the problem of plasticity dropping after the existing stainless steel materials improved the yield strength, and achieved a synergistic effect of high strength and good plasticity.
Patent Information
- Application Number
- CN202411806345.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-28
AI Technical Summary
After the existing stainless steel materials have improved the yield strength, the plasticity has dropped significantly, resulting in a strong plasticity trade-off. The gradient grain structure is limited in the formation of the material surface, making it difficult to apply in industrial large-scale production.
Through axial cold rolling and heat treatment methods, stainless steel sheets with austenite grain size and martensite phase content are prepared in a gradient distribution from the center to the edge, achieving a double gradient distribution of grain size and phase content.
This method effectively improves the strength of stainless steel sheets, while retaining good plasticity, achieving excellent strong plasticity characteristics, and is suitable for industrial large-scale production.
Smart Images

Figure CN119530652A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material processing, in particular to a stainless steel sheet suitable for double gradient distribution of grain size and martensite phase and a preparation method thereof. Background Art
[0002] Stainless steel is an important metal material. Its unique properties make it widely used in industries such as construction, manufacturing, automobiles, ships, and aerospace. The main advantages of stainless steel include wear resistance, corrosion resistance, high plasticity, and high toughness, which enable it to maintain good performance in extreme environments. However, despite the many advantages of stainless steel, its relatively low strength limits its application in higher strength fields.
[0003] Yield strength is an important indicator to measure whether a material can withstand external forces without permanent deformation. Plasticity is the ability of a material to deform when subjected to external forces. For high-strength materials, good plasticity not only helps with processing and forming, but also improves the safety of components.
[0004] After cold rolling and heat treatment of plate-like materials, uniform grain size and phase content can be obtained, and the yield strength can be improved, but it often leads to a significant decrease in plasticity, resulting in a serious trade-off between strength and plasticity. The preparation of gradient grain structure can improve this situation, which is generally prepared by surface mechanical grinding and surface mechanical rolling, but its structure only forms a micron-level thickness on the surface of the material, and this method is only applicable to smaller-sized raw materials, which limits its application in industrial large-scale production. The present invention provides a stainless steel sheet with a dual gradient distribution of grain size and martensitic phase and a preparation method thereof. Summary of the invention
[0005] In order to overcome the problems existing in the prior art, the present invention provides the following technical solutions: The invention provides a stainless steel sheet with a dual gradient distribution of grain size and martensite phase. The constituent elements of the stainless steel sheet are as follows by mass percentage: 18-22wt% Cr, 7-9wt% Ni, 0.8-1.5wt% Mn, 0.4-1.2wt% Si, and the rest are Fe and inevitable impurities.
[0006] Preferably, the unavoidable impurities include: 0.03wt%P, 0.03wt%N, 0.04wt%C and 0.001wt%S.
[0007] Preferably, in the microstructure of the stainless steel sheet, the austenite grain size and the martensite grain size are distributed in a gradient from the center to the edge, and the martensite phase content is distributed in a gradient from the edge to the center.
[0008] Preferably, the austenite grain size at the center of the stainless steel sheet is 1.64~2.26μm, and the austenite grain size at the edge is 2.01~2.33μm; the martensite grain size at the center of the stainless steel sheet is 1.29~1.4μm, and the martensite grain size at the edge is 1.39~1.49μm; the martensite phase content at the center of the stainless steel sheet is 4.6%~15.2%, and the martensite phase content at the edge is 3.9%~9.2%.
[0009] The present invention also provides a method for preparing a stainless steel sheet with a dual gradient distribution of grain size and martensite phase, the preparation method comprising the following steps: S1. Weigh an appropriate amount of pure Cr, pure Ni, pure Mn, pure Si and pure Fe with a purity of not less than 99.9% as raw materials, mix them according to the above-mentioned stainless steel sheet element ratio, and then melt them in a vacuum medium frequency induction melting furnace to obtain stainless steel bars with a cross-sectional diameter of 6mm~12mm; S2, subjecting the prepared stainless steel bar to axial cold rolling to obtain a stainless steel sheet with a thickness of 2 mm; S3. The stainless steel sheet after axial cold rolling is heat treated, and after water quenching, a stainless steel sheet with a double gradient distribution of grain size and martensite phase is obtained.
[0010] Preferably, the axial cold rolling in step S2 is performed by a twin-roll mill; during the axial cold rolling of the stainless steel bar, the twin-roll mill applies 65-85% reduction to the center of the stainless steel bar and 0% reduction to the sides of the stainless steel bar.
[0011] Preferably, the heat treatment in step S3 is carried out at a holding temperature of 700 to 900° C. and a holding time of 10 to 30 minutes.
[0012] Compared with the prior art, the present invention has the following beneficial technical effects: The stainless steel sheet with dual gradient distribution of grain size and martensite phase prepared by the present invention realizes dual gradient changes in martensite and austenite grain sizes and martensite phase content. The dual gradient distribution of grain size and martensite phase content refines the average grain size in the central area of the stainless steel sheet, and the martensite content is relatively high, thereby effectively improving the strength of the material. At the same time, the coarse-grained structure retained at the edge and the lower martensite content ensure that the material has good plasticity. The combined effect of the two makes the stainless steel sheet with gradient grain size and martensite phase content show excellent strong and plastic characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings of the embodiments will be briefly described below. It should be noted that the drawings described below only relate to some embodiments of the present disclosure, but are not intended to limit the present disclosure, wherein: Figure 1 It is a schematic diagram of the preparation process provided by the present invention.
[0014] Figure 2 1 is an electron backscatter diffraction (EBSD) diagram of the stainless steel sheet obtained in Example 1 of the present invention, wherein a is the central structure diagram of the stainless steel sheet obtained in Example 1, and b is the edge structure diagram of the stainless steel sheet obtained in Example 1.
[0015] Figure 3 1 is an electron backscatter diffraction (EBSD) diagram of the stainless steel sheet obtained in Example 2 of the present invention, wherein c is the central structure diagram of the stainless steel sheet obtained in Example 2, and d is the edge structure diagram of the stainless steel sheet obtained in Example 2.
[0016] Figure 4 3 is an electron backscatter diffraction (EBSD) diagram of the stainless steel sheet obtained in Example 3 of the present invention, wherein e is the central structure diagram of the stainless steel sheet obtained in Example 3, and f is the edge structure diagram of the stainless steel sheet obtained in Example 3.
[0017] Figure 5 3 is the cross-sectional Vickers microhardness distribution curve of the stainless steel thin plates obtained in Example 1, Example 2 and Example 3 of the present invention.
[0018] Figure 6 It is the uniaxial tensile engineering stress-strain curve of the stainless steel thin plates obtained in Example 1, Example 2 and Example 3 of the present invention. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the embodiments of the present disclosure clearer, the technical solution of the embodiments of the present disclosure will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by those skilled in the art without creative work also fall within the scope of protection of the present disclosure.
[0020] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by a person skilled in the art to which the subject matter of the present disclosure belongs. It will be further understood that terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the specification and the relevant art, and will not be interpreted in an idealized or overly formal form unless otherwise explicitly defined herein. As used herein, a statement that two or more parts are "connected" or "coupled" together shall mean that the parts are joined together directly or through one or more intermediate components.
[0021] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase "embodiments" in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0022] In one aspect, the present invention provides a stainless steel sheet having a dual gradient distribution of grain size and martensite phase, wherein the constituent elements of the stainless steel sheet are preferably: 18-22wt% Cr, for example, 18wt%, 19.85wt%, 20.36wt%, 21wt%, 22wt%, etc.; 7-9wt% Ni, for example, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, etc.; 0.8-1.5wt% Mn, for example, 0.8wt%, 0.9wt%, 1.1wt%, 1.3wt%, 1.5wt%, etc.; 0.4-1.2wt% Si, for example, 0.4wt%, 0.5wt%, 0.7wt%, 0.9wt%, 1.2wt%, etc.; The rest is Fe and inevitable impurities, and the inevitable impurities include: 0.03wt%P, 0.03wt%N, 0.04wt%C and 0.001wt%S.
[0023] In the present invention, in the microstructure of the stainless steel sheet, the austenite grain size and the martensite grain size are distributed in a gradient from the center to the edge, and the martensite phase content is distributed in a gradient from the edge to the center; the austenite grain size at the center of the stainless steel sheet is preferably 1.64-2.26 μm, for example, it can be 1.64 μm, 1.73 μm, 1.81 μm, 1.95 μm, 2.1 μm, 2.15 μm, 2.2 μm, 2.26 μm, etc., and the austenite grain size at the edge is preferably 2.01-2.33 μm, for example, it can be 2.01 μm, 2.15 μm, 2.2 μm, 2.25 μm, 2.28 μm, 2.33 μm, etc.; the martensite grain size at the center of the stainless steel sheet is preferably 1.29-1.4 μm, for example, it can be 1 .29μm, 1.31μm, 1.33μm, 1.35μm, 1.37μm, 1.4μm, etc., the martensite grain size at the edge is preferably 1.39~1.49μm, for example, it can be 1.39μm, 1.41μm, 1.43μm, 1.45μm, 1.47μm, 1.49μm, etc.; the martensite phase content in the center of the stainless steel sheet is preferably 4.6%~15.2%, for example, it can be 4.6%, 5.5%, 6.5%, 7.8%, 8.9%, 9.3%, 11.5%, 13.5%, 14.1%, 15.2%, etc., and the martensite phase content at the edge is preferably 3.9%~9.2%, for example, it can be 4.5%, 5.5%, 6.5%, 7.8%, 8.5%, 9.2%, etc.
[0024] The present invention also provides a method for preparing a stainless steel sheet with a dual gradient distribution of grain size and martensite phase, the preparation method comprising the following steps: S1. Weigh an appropriate amount of pure Cr, pure Ni, pure Mn, pure Si and pure Fe with a purity of not less than 99.9% as raw materials, mix them according to the above-mentioned stainless steel sheet element ratio, and then melt them in a vacuum medium frequency induction melting furnace to obtain a stainless steel bar with a cross-sectional diameter of preferably 6mm to 12mm. The cross-sectional diameter can be 6mm, 8mm, 10mm, or 12mm; S2, subjecting the prepared stainless steel bar to axial cold rolling to obtain a stainless steel sheet with a thickness of 2 mm; S3, heat treating the stainless steel sheet after axial cold rolling, and quenching it with water to room temperature to obtain a stainless steel sheet with a double gradient distribution of grain size and martensite phase; Among them, the holding temperature of the heat treatment is preferably 700-900°C, for example, it can be 700°C, 720°C, 750°C, 800°C, 850°C, 880°C, 900°C, etc., and the holding time is preferably 10-30 min, for example, it can be 12min, 15min, 17min, 20min, etc.
[0025] The following is explained in conjunction with specific embodiments: Example 1
[0026] A stainless steel sheet with a dual gradient distribution of grain size and martensite phase has the following constituent elements and mass percentages: 18.02wt% Cr, 8.04wt% Ni, 1.04wt% Mn, 0.47wt% Si, 0.04wt% C, 0.03wt% P, 0.03wt% N, 0.001wt% S, and the remainder is Fe; The method for preparing a stainless steel sheet with a dual gradient distribution of grain size and martensite phase comprises the following steps: Weigh appropriate amounts of pure Cr, pure Ni, pure Mn, pure Si and pure Fe with a purity of not less than 99.9% as raw materials, mix them according to the above-mentioned stainless steel sheet element ratio, and then melt them in a vacuum medium frequency induction melting furnace to obtain a stainless steel bar with a cross-sectional diameter of 8 mm; then perform axial cold rolling to roll it into a stainless steel sheet with a thickness of 2 mm; The cold-rolled stainless steel sheet was cut into block specimens along the cross section, placed in a box furnace at 750 °C for 15 min, and then quenched with water to room temperature (25 °C) to obtain stainless steel sheet plate specimens with gradient grain size and phase content, such as Figure 1 shown.
[0027] The block specimens prepared by the above method were subjected to performance tests, and the test results are as follows: EBSD analysis of the cross section of the specimen showed that the austenite grain size increased from 1.64 μm in the center to 2.01 μm at the edge; the martensite grain size increased from 1.40 μm in the center to 1.44 μm at the edge, and the martensite content increased from 9.2% at the edge to 15.2% in the center. Figure 2 (a, b). It can be concluded that after cold rolling and heat treatment, the center grain size of the stainless steel thin sheet is smaller than that of the two sides and the center martensite content is higher.
[0028] The hardness of the specimen at different locations on the cross section was tested using a Vickers microhardness tester. Figure 5 As shown in the figure, the Vickers microhardness test found that the Vickers hardness increased continuously from 254.72 HV and 254.13 HV at the sides of the cross section to 266.38 HV at the center. The Vickers hardness has the same distribution trend as the average grain size and martensite content, indicating that under the combined effect of grain size and martensite content, the hardness of the stainless steel sheet increases from the sides to the center.
[0029] like Figure 6As shown in the figure, the yield strength of the stainless steel sheet after cold rolling and heat treatment is increased to 528.27 MPa, and the tensile strength is increased to 877.93 MPa. At the same time, its plasticity is retained to 42.86%. Compared with 304 coarse-grained austenitic stainless steel (yield strength of 330.93 MPa, tensile strength of 627.17 MPa, and plasticity of 63.15%), the yield strength is increased by 59.63% and the tensile strength is increased by 39.98%. The dual gradient distribution of grain size and martensite phase content refines the average grain size in the central area of the stainless steel sheet and has a high martensite content, which effectively improves the material strength; at the same time, the coarse-grained structure and low martensite content retained at the edge ensure that the material has good plasticity. The combined effect of the two makes the gradient grain size and phase content stainless steel sheet show excellent strength and plasticity characteristics. Example 2
[0030] The stainless steel sheet after axial cold rolling in Example 1 was cut into block samples along the cross section and placed in a box furnace at 800°C for 15 min, and then water quenched to room temperature (25°C) to obtain stainless steel sheet plate samples with gradient grain size and phase content.
[0031] The performance test of the block sample prepared by the above method is carried out, and the test results are as follows: EBSD analysis of the cross section of the sample shows that the austenite grain size increases from 1.74 μm in the center to 2.02 μm at the edge; the martensite grain size increases from 1.29 μm in the center to 1.39 μm at the edge, and the martensite content increases from 3.9% at the edge to 4.6% in the center. Figure 3 (c, d). It can be concluded that after cold rolling and heat treatment, the center grain size of the stainless steel thin sheet is smaller than that of the two sides and the center martensite content is higher.
[0032] The hardness of the specimen at different locations on the cross section was tested using a Vickers microhardness tester. Figure 5 As shown in the figure, the Vickers microhardness test found that the Vickers hardness increased continuously from 236.81 HV and 238.06 HV at the edges of the cross section to 254.76 HV at the center. It can be seen that the hardness of the stainless steel sheet increases gradually from the edges to the center.
[0033] like Figure 6 As shown in the figure, the yield strength of the stainless steel sheet after cold rolling and heat treatment is increased to 491.08 MPa, and the tensile strength is increased to 870.44 MPa. At the same time, its plasticity is retained to 45.11%. Compared with 304 coarse-grained austenitic stainless steel, the yield strength is increased by 48.39% and the tensile strength is increased by 38.79%, achieving the synergy of strength and plasticity. Example 3
[0034] The stainless steel sheet after axial cold rolling in Example 1 was cut into block samples along the cross section and placed in a box furnace at 850°C for 15 min, and then water quenched to room temperature (25°C) to obtain stainless steel sheet plate samples with gradient grain size and phase content.
[0035] The block specimens prepared by the above method were tested for performance, and the test results are as follows: EBSD analysis of the cross section of the specimen showed that the austenite grain size increased from 2.26 μm in the center to 2.33 μm at the edge; the martensite grain size increased from 1.29 μm in the center to 1.49 μm at the edge, and the martensite content increased from 4.0% at the edge to 7.9% in the center. Figure 4 (e, f). It can be concluded that after cold rolling and heat treatment, the center grain size of the stainless steel thin sheet is smaller than that of the two sides and the center martensite content is higher.
[0036] The hardness of the specimen at different locations on the cross section was tested using a Vickers microhardness tester. Figure 5 As shown in the figure, the Vickers microhardness test found that the Vickers hardness increased continuously from 220.14 HV and 223.54 HV at the sides to 231.27 HV at the center. It can be seen that the hardness of the stainless steel sheet increases gradually from the sides to the center.
[0037] like Figure 6 As shown in the figure, the yield strength of the stainless steel sheet after cold rolling and heat treatment is increased by 401.92 MPa, and the tensile strength is increased to 875.23 MPa. At the same time, its plasticity is retained to 46.21%. Compared with 304 coarse-grained austenitic stainless steel, the yield strength is increased by 21.45% and the tensile strength is increased by 39.55%, achieving the synergy of strength and plasticity.
[0038] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A stainless steel sheet with a dual gradient distribution of grain size and martensite phase, characterized in that: The composition elements of the stainless steel sheet are as follows by mass percentage: 18-22wt% Cr, 7-9wt% Ni, 0.8-1.5wt% Mn, 0.4-1.2wt% Si, and the rest are Fe and inevitable impurities.
2. The stainless steel sheet with dual gradient distribution of grain size and martensite phase according to claim 1, characterized in that: The unavoidable impurities include: 0.03wt%P, 0.03wt%N, 0.04wt%C and 0.001wt%S.
3. The stainless steel sheet with dual gradient distribution of grain size and martensite phase according to claim 1, characterized in that: In the microstructure of the stainless steel sheet, the austenite grain size and the martensite grain size are distributed in a gradient from the center to the edge, and the martensite phase content is distributed in a gradient from the edge to the center.
4. The stainless steel sheet with dual gradient distribution of grain size and martensite phase according to claim 3, characterized in that: The austenite grain size in the center of the stainless steel sheet is 1.64~2.26μm, and the austenite grain size at the edge is 2.01~2.33μm; the martensite grain size in the center of the stainless steel sheet is 1.29~1.4μm, and the martensite grain size at the edge is 1.39~1.49μm; the martensite phase content in the center of the stainless steel sheet is 4.6%~15.2%, and the martensite phase content at the edge is 3.9%~9.2%.
5. The method for preparing a stainless steel sheet having a dual gradient distribution of grain size and martensite phase according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1. Weigh an appropriate amount of pure Cr, pure Ni, pure Mn, pure Si and pure Fe with a purity of not less than 99.9% as raw materials, mix them according to the above-mentioned stainless steel sheet element ratio, and then melt them in a vacuum medium frequency induction melting furnace to obtain stainless steel bars with a cross-sectional diameter of 6mm~12mm; S2, subjecting the prepared stainless steel bar to axial cold rolling to obtain a stainless steel sheet with a thickness of 2 mm; S3. The stainless steel sheet after axial cold rolling is heat treated, and after water quenching, a stainless steel sheet with a double gradient distribution of grain size and martensite phase is obtained.
6. The method for preparing a stainless steel sheet with a dual gradient distribution of grain size and martensite phase according to claim 5, characterized in that: The axial cold rolling in step S2 is performed by a twin-roll mill; during the axial cold rolling of the stainless steel bar, the twin-roll mill applies 65-85% reduction to the center of the stainless steel bar and 0% reduction to the sides of the stainless steel bar.
7. The method for preparing a stainless steel sheet with a dual gradient distribution of grain size and martensite phase according to claim 5, characterized in that: The heat treatment in step S3 is carried out at a holding temperature of 700 to 900° C. and a holding time of 10 to 30 minutes.
Citation Information
Cited By
Preparation method of stainless steel thin strip based on Ce modification solid-solution-free gradient aging strengthening
CN121137442A
A method for preparing stainless steel strips based on Ce-modified solution-free gradient aging strengthening
CN121137442B